KEEFEKTIFAN MODEL PEMBELAJARAN GROUP INVESTIGATION PADA MATA PELAJARAN IPA KELAS VI SDN 016 MARSAWA - Dasinah Dasinah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
Effective learning will not arise by itself. The teacher must create learning that allows students to achieve goals that have been set optimally, especially in Natural Sciences subjects. The fact that happened in the field, there are still many implementation of learning that do not utilize and use good learning resources, and teachers only use that method. This problem causes the learning taught to be unattractive and boring for students. To streamline the process of learning and improve student learning outcomes, the researcher applied a cooperative learning model type investigation group. The results of the study showed, in the first cycle, students who completed as many as 25 people and students who did not complete by 12 people with a percentage of completeness of 67.5. After the second cycle, students who complete improved this is evidenced by students who completed 32 people and students who did not complete by 5 people with a percentage of completeness of 86.4%. with these results it can be concluded that the investigation group learning model can streamline the learning process of students and can improve the learning outcomes of class VI students of 016 Marsawa Public Elementary School